Comparison of Surgery and Prolonged Spironolactone Therapy in Patients with Hypertension, Aldosterone Excess, and Low Plasma Renin. Issue 5816 (24th June 1972) - Brown, J. J.; Davies, D. L.; Ferriss, J. B.; Fraser, R.; Haywood, E.; Lever, A. F.; Robertson, J. I. S.
Abstract : The effect of prolonged preoperative treatment with spironolactone has been studied in a series of 67 patients with hypertension, aldosterone excess, and low plasma renin. In the series as a whole a highly significant reduction in both systolic and diastolic pressures was achieved, with no evidence of escape from control during therapy lasting several years in some cases. The drug was equally effective in controlling blood pressure in patients with and without adrenocortical adenomata. Occasional unresponsive patients were encountered in both groups; pretreatment blood urea levels in these were significantly higher than in the responsive patients. The hypotensive effect of spironolactone usually predicted the subsequent response to adrenal surgery. Spironolactone in all cases corrected plasma electrolyte abnormalities; significant increases in total exchangeable (or total body) potassium and significant reductions in total exchangeable sodium, total body water, extracellular fluid, and plasma volumes were seen. Plasma urea rose during treatment and there was a slight fall in mean body weight. Significant increases in peripheral venous plasma renin and angiotensin II concentrations occurred during treatment. In two patients no increase in aldosterone secretion rate was found during treatment, although plasma aldosterone rose in three of four subjects studied. Severe side effects were rare; in only two of the 67 patients did the drug have to be stopped. In addition to its routine preoperative use, spironolactone can now be advised as long-term therapy in selected patients.